2012
DOI: 10.1016/j.neuroimage.2011.08.077
|View full text |Cite
|
Sign up to set email alerts
|

MRI estimates of brain iron concentration in normal aging using quantitative susceptibility mapping

Abstract: Quantifying tissue iron concentration in vivo is instrumental for understanding the role of iron in physiology and in neurological diseases associated with abnormal iron distribution. Herein, we use recently-developed Quantitative Susceptibility Mapping (QSM) methodology to estimate the tissue magnetic susceptibility based on MRI signal phase. To investigate the effect of different regularization choices, we implement and compare ℓ1 and ℓ2 norm regularized QSM algorithms. These regularized approaches solve for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
425
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(480 citation statements)
references
References 37 publications
50
425
1
4
Order By: Relevance
“…If only these two sources of contrast contribute to the three quantitative maps, the number of measurements is greater than the number of unknowns even when the relaxivity and baseline values are unknown, provided that the number of measurements is greater than nine. In order to increase the reliability of the fitting procedure, the iron coefficients to susceptibility (0.73×10 -3 ppm/(mg/ Kg)) and R 2 * (0.242 Hz/(mg/Kg)) were assumed as reported in Lim et al (2013) and using the slope observed between R 2 * and susceptibility reported by Deistung et al (2013) in deep grey matter structures at 7 T. These values are in close agreement with those obtained in other studies (Bilgic et al, 2012;Langkammer et al, 2012Langkammer et al, , 2010Schweser et al, 2011;Bowtell, 2013, 2010). The use of these parameters implies the calculated iron concentration will be in mg/Kg.…”
Section: Iron and Myelin Mapssupporting
confidence: 81%
See 1 more Smart Citation
“…If only these two sources of contrast contribute to the three quantitative maps, the number of measurements is greater than the number of unknowns even when the relaxivity and baseline values are unknown, provided that the number of measurements is greater than nine. In order to increase the reliability of the fitting procedure, the iron coefficients to susceptibility (0.73×10 -3 ppm/(mg/ Kg)) and R 2 * (0.242 Hz/(mg/Kg)) were assumed as reported in Lim et al (2013) and using the slope observed between R 2 * and susceptibility reported by Deistung et al (2013) in deep grey matter structures at 7 T. These values are in close agreement with those obtained in other studies (Bilgic et al, 2012;Langkammer et al, 2012Langkammer et al, , 2010Schweser et al, 2011;Bowtell, 2013, 2010). The use of these parameters implies the calculated iron concentration will be in mg/Kg.…”
Section: Iron and Myelin Mapssupporting
confidence: 81%
“…Iron concentration in deep gray matter structures (globus pallidus, putamen, caudate) have been shown to have a correlation with susceptibility (Bilgic et al, 2012;Langkammer et al, 2012;Lim et al, 2013;Schweser et al, 2011;Bowtell, 2013, 2010). Myelin content does contribute to the gray and white matter contrast in phase imaging (C. Liu et al, 2011;Lodygensky et al, 2012) yet, not only is the myelin susceptibility anisotropic, its contribution to the measured phase images is driven by the microstructural compartmentalization of lipid organization and its orientation in respect to the static magnetic field (He and Yablonskiy, 2009;Luo et al, 2014;Wharton and Bowtell, 2013;Yablonskiy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Iron contributes to tissue contrast especially in the deep gray matter (globus pallidus, putamen and caudate) which has histologically derived high iron concentration showing good correlation with phase and susceptibility contrast (Bilgic et al, 2012;Schweser et al, 2011;Wharton and Bowtell, 2010). The other proposed contributor to the phase contrast, particularly between white and gray matter, is myelin where pathological demyelination has shown a decreased phase contrast between gray and white matter (C. Liu et al, 2011;Lodygensky et al, 2012) and good correlation was found between myelination and phase contrast during development.…”
Section: Introductionmentioning
confidence: 99%
“…70 In addition to T1-and T2-weighted imaging, high-resolution quantitative techniques such as R2*, susceptibility-weighted imaging, and quantitative susceptibility maps have shown promise in detecting microbleeds in vascular dementia, quantifying iron content in normal aging, and as a tool for assessing hippocampal subfield differences. 10,31,85 Hence, these techniques may play a role in detecting neuroanatomical atrophy and visualizing microinfarcts in AD, as well as providing insights to better understand the role of iron and inflammation in the progression of the disease.…”
Section: Future Of 7-t Imaging In Admentioning
confidence: 99%